Pengembangan Media Pembelajaran Interaktif Mata Pelajaran Desain Grafis Percetakan menggunakan Model Four-D pada Siswa SMK Negeri 5 Malang - Fajar Ramadhanti; Hanifah Muslimah Az-Zahra; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The study aims to determine the validity of interactive learning media on graphic design subjects of printing using the four-D model and know the level of understanding of learners after receiving learning. Interactive learning Media helps the interaction between teachers and learners in learning. The methods used in this research are research and development using four-D models. The research consists of four phases, namely (1) definition, (2) planning, (3) development, and (4) dissemination. Subjects in the study were students of class XI Multimedia 1 SMK Negeri 5 Malang. The instruments used include interactive learning media validation sheets, multiple choice tests including pretests and posttest, assessment sheets, learners ' response questionnaire. Based on the results of the study obtained that: (1) Interactive learning Media-based e-books graphic design printing is declared worthy based on the validation results with an average validation result by a validator of 87%, it indicates that Media that is made valid with the category